PERAN KOMPETENSI PEDAGOGIK, KEPRIBADIAN, PROFESIONAL, DAN SOSIAL GURU TERHADAP PRESTASI BELAJAR SISWA DI SD NEGERI 3 JANGKRIKAN - Febriana Devista Nurul Cahyani; Diza Sekar Agianti; Permata Diva Ramadhani; Hermawan Wahyu Setiadi (STKIP Subang, 2026)
This study aims to describe the role of pedagogic competence, personality competence, professional competence, and social competence of teachers on student learning achievement at SD Negeri 3 Jangkrikan. The research uses a qualitative approach with a descriptive method. Data was obtained through interviews with grade IV teachers of SD Negeri 3 Jangkrikan and supported by documentation studies and relevant literature studies. Data analysis was carried out descriptively to understand the phenomenon that occurred in depth based on real conditions in the field. The results of the study show that teachers' pedagogic competence plays a role in improving student learning achievement through the ability to manage classes, design learning, and use various learning methods and media. Teachers' personality competencies contribute through example, the ability to manage emotions, and create a comfortable learning environment so as to increase students' motivation to learn. Teachers' professional competence can be seen from mastery of learning materials, the use of technology, and sustainable self-development efforts that support learning effectiveness. Meanwhile, teachers' social competence plays a role in building good communication with students, colleagues, and parents so as to create an inclusive and conducive learning environment.